Balinese Muslim Minority Rights in Education and Islamic Family Law - Muhammad, Ismail; Ariani, Safrina; Yusuf, Muhammad (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2021)
Islam came in peace to Bali in the 14th century, initiated by communities from Java, and followed by those from Bugis, Makassar, Lombok, and even Malays and Arabs. Muslims in Bali are a minority group, which only accounts for 10.08% of the total population of Bali. This study aims to examine the rights of the Balinese Muslim minority in education and Islamic family law. This study is empirical legal research that examines the law in relation to problems in society realistically, or a socio-legal study, using a phenomenological approach. Data collection techniques included interview, observation, and literature review. The respondents interviewed were selected purposively from the Regional Office of the Ministry of Religious Affairs, the Mosque Management, the Provincial Council of Ulema, and the local Muslim community. The findings reveal that the rights of Balinese Muslim minority in terms of education, both formal and informal, are displayed through strengthening the family resilience by building the spirit of Islam, carrying out children’s education in an Islamic way by promoting tolerance, and sending children to Islamiceducational institutions such as Taman Pendidikan Al-Qur' an (TPA), Raudhatul Atfhal (RA), pesantrens, and madrasas. Further, Islamic family law is implemented in matters of marriage, divorce, waqf, child guardianship, and joint property under the simple, fast, and low-cost principles carried out by the Office of Religious Affairs, Religious Counselors, and the Religious Courts in Denpasar. It seems that historical bonding is highly fundamental that allows the Muslims and the Balinese people in general to continue to live in harmony and peace to this day.